Horizon : an American saga. Chapter 1 [videorecording (DVD)] - Costner, Kevin; Costner, Kevin; Baird, Jon; Kasdan, Mark; Miller, Sienna, 1981-; Worthington, Sam, 1976-; Ribisi, Giovanni, 1974-; Abbey Lee, 1987-; Patton, Will; Malone, Jena, 1984-; Rooker, Michael, 1955-; Huston, Danny, 1962-; et al. (Warner Bros. Entertainment Inc., 2024)
Explores the lure of the Old West and how it was won, and lost, through the blood, sweat and tears of many. Spanning the four years of the Civil War, from 1861 to 1865, Kevin Costner's ambitious cinematic adventure will take audiences on an emotional journey across a country at war with itself, experienced through the lens of families, friends and foes all attempting to discover what it truly means to be the United States of America.